Wild-type Yellow fever virus in cerebrospinal fluid from fatal cases in Brazil, 2018 - Rezende, Izabela Mauricio de; Cenachi, Adriana Regina Campolina; Costa, Thais Alkifeles; Oliveira, Gabriela Fernanda Garcia; Rabelo, Livia; Menezes, Leticia Mattos; Penido, Indiara; Pereira, Leonardo Soares; Arruda, Matheus Soares; Gonçalves, Andreza Parreiras; Alves, Pedro Augusto; Kroon, Erna Geessien; et al. (Frontiers in Virology, 2022)
Yellow fever virus (YFV) is the causative agent of yellow fever (YF), a hemorrhagic and viscerotropic known acute disease. Severe YF had been described in approximately 15-25% of YF patients, with 20-50% of severe YF cases being fatal. Here we analyzed cerebrospinal fluid (CSF) samples collected during the YF outbreak in Brazil in 2018, aiming to investigate CNS neuroinvasion in fatal YFV. YFV RNA was screened by RT-qPCR targeting the 3’UTR region of the YFV genome in CSF. CSF samples was tested for the presence of anti-YFV IgM and neutralizing antibodies, coupled with routine laboratory exams. Among the 13 patients studied, we could detect anti-YFV IgM in CSF from eight patients and YFV RNA in CSF from five patients, presenting severe YF. YFV RNA genomic load in CSF samples ranged from 1.75x103 to 5.42x103 RNA copies/mL. We genotyped YFV from three CSF samples that grouped with other YFV samples from the 2018 outbreak in Brazil within the South-American I genotype. Even though descriptions of neurologic manifestations due to wild type YFV(WT-YFV) infection are rare, since the last YF outbreak in Brazil in 2017-2018, a few studies have demonstrated WT-YFV RNA in CSF samples from YF fatal cases. Serological tests indicated the presence of IgM and neutralizing antibodies against YFV in CSF samples from two patients. Although the presence of viral RNA, IgM and neutralizing antibodies in CSF samples could indicate neuroinvasiveness, further studies are needed to better elucidate the role of YFV neuroinvasion and possible impacts in disease pathogenesis.